Postcholecystectomy Iatrogenic Biliary Injury Presentation, Diagnosis and Management at the National Centre of Gastroeneterology and Liver Disease - Sudan (Global Journal of Medical Research, 2014)
Background: Iatrogenic biliary duct injury is a rare but potentially devastating condition associated with significant morbidity and mortality. Related data are limited in developing countries. This study aimed to analyse the clinical presentation, diagnosing and type of biliary injuries, and management proposed and in a population treated at a tertiary care centre. Method : Retrospective and prospective analysis of patients who sustained IBDI, and presented to the Gastroeneterology surgical department at the National Centre Of Gastroenterolgy and Liver Disease Sudan , between the period of October 2010 to September 2013 (three years period). Results : Total of 40 patients diagnosed as IBDI, 36 were females and 4 were males. Their mean age was 41 years (range 23-72) years. IBDI were due to 90% (n=36) post OC and due to10% (n= 4 ) post LC. 65%presented with obstructive jaundice, 20% presented with biliary peritonitis, 15% presented with biliary cutaneous fistula (bile leak). The identification rate of intra-operative injury was 10% and 90% in the post-operative group. Time of presentation ranged between 2 days and 3 years the median was12 days .According to Strasberg type E I, II, III and type D injuries, 20%, 37.5%,35%,7.5% were seen in patients, respectively. 87.5% of patients (n=35) underwent Roux en Y HJ. 5% of patients (n=2) underwent ERCP stenting, 2.5% underwent end to end anastamosis , 2.5% underwent primary repair T tube insertion.. Fifteen patients (40.5%) had complications during their hospital stay. Total hospitalization days, ranged between 14 days and 1months the median was 18 days. Mortality was 12.5% (n=5). Conclusion : Open cholecystectomy is the main cause of IBDI in our study. In most of the cases surgical reconstruction with hepaticojejunostomy was required as the definitive treatment. ERCP should only be attempted when there is biliary continuity Intrabdominal abscess is the most common cause of death. Early referral to a tertiary centre with exp
Keywords: open cholecystectomy; biliary injury; strasberg classification